Acting for nature what young people around the world have done to protect the environment - Collard, Sneed B.; Buell, Carl Dennis (Berkeley, Calif. Heyday Books, 2000)
Describes the efforts of fifteen young people to protect the environment in their communities in different countries around the world.
Keywords: Child environmentalists -- Case studies -- Juvenile literature; Environmental protection; Conservation of natural resources